Perceptual Grouping During Binocular Rivalry in Mild Glaucoma - Issashar Leibovitzh, Galia; Trope, Graham E.; Buys, Yvonne M.; Tarita-Nistor, Luminita (Frontiers in Aging Neuroscience, 2022)
Purpose: This study tested perceptual grouping during binocular rivalry to probe the strength of neural connectivity of the visual cortex involved in early visual processing in patients with mild glaucoma. Methods: Seventeen patients with mild glaucoma with no significant visual field defects and 14 healthy controls participated. Rivalry stimuli were 1.8 deg-diameter discs, containing horizontal or vertical sine-wave gratings, viewed dichoptically. To test grouping, 2 spatially separated identical stimuli were presented eccentrically to the same or different eyes and to the same or different hemifields. The outcome measures were time of exclusive dominance of the grouped percept (i.e., percept with synchronized orientations), rivalry rate, and epochs of exclusive dominance. Results: For both groups, grouping occurred primarily for the matching orientations in the same eye/same hemifield (MO SE/SH) and for the matching orientations in the same eye/different hemifield (MO SE/DH) conditions. Time dominance of the grouped percept of the glaucoma group was similar to that of the control group in all conditions. Rivalry rates in the MO SE/SH and MO SE/DH conditions were significantly larger in the control group than in the glaucoma group. The epochs of exclusive dominance of the grouped percept in the MO SE/SH condition were a median of 48ms longer for the control group, but a median of 116ms shorter for the glaucoma group when compared to those in the MO SE/DH condition. Conclusions: Patients with mild glaucoma show clear impairments in binocular rivalry while evidence for deficits in perceptual grouping could be inferred only indirectly. If these deficits truly exist, they may have implications for higher levels of visual processing such as object recognition and scene segmentation, but these predictions remain to be tested in future studies.